Development and Evaluation of Nipa (Nypa Fruticans) Vinegar Powder - De Castro Jr., Mario A. (JPAIR Multidisciplinary Research, 2018)
Due to emerging technologies, the improvization of products is a new trend. Spray drying is a new technology that transforms a product in liquid phase into a dry particulate powder. This study investigated the possibility of developing powder out of nipa vinegar with ideal physicochemical properties and high recovery percentage. A single process schedule design was applied in the nipa vinegar during spray drying. Three formulations of the added carrier were applied (F1- 50%, F2- 25% and F3-12.50%). The sensory characteristics of the spray-dried nipa vinegar in three formulations were analyzed and compared using organoleptic evaluation score card utilized by food experts. The pH level, total soluble solids (TSS) and solubility test of the three samples were also measured. Results showed that nipa vinegar with 12.50% of the added carrier is the preferred sample by the respondents and has the fastest solubility rate. However, it has the lowest recovery percentage. On the other hand, the nipa vinegar with 50% added carrier has the highest recovery percentage. The three samples have consistent pH value and changes were only observed in Nipa Vinegar with 50% added carrier. Further studies should be conducted to optimize the production quality of spray-dried nipa vinegar.
Keywords: Food processing; nipa vinegar; pH level; quality attributes; recovery percentage; total soluble solids (TSS); spray drying; MIMAROPA Food Innovation Center; Philippines